Leadership and entrepreneurship: a case of Redhill Herbals Pvt. Ltd. - Singh, Harjit; Singh, Ramanjeet; Kota, Hima Bindu (Serbian Journal of Management, 2018)
This research work seeks to investigate the issues that inspire an entrepreneur to be successful in his entrepreneurial journey. Mediating role of influence and vision are viewed as inevitable resources for strategic entrepreneurship. The paper sheds lights on the leadership style and analyses the issues related to influence, motivate, restructuring, and contribute to the field's growing body of work. The research study employs a case study method. The interviewees were interviewed by theme questions and secondary information was gathered to strengthen the empirical section. The findings demonstrate that a successful organisation comes in existence not only because of the efforts put in by self-motivated individual who is ready to undertake responsibility of leading and taking risks. This necessitates distinctive quality on the part of an entrepreneur who is always cognizant of the new developments and vagaries surrounding him and does not hesitate to adapt to those changes. The case presents an opportunity for burgeoning entrepreneurs and would-be managers to comprehend how leadership style and entrepreneurial context guarantee entrepreneurial success.
Keywords: opportunities; leadership styles; LEADERSHIP; entrepreneurship; challenge